SAT0267 SERUM ANTI-HETEROGENEOUS NUCLEAR RIBONUCLEOPROTEIN ANTIBODY CHARACTERIZES SYSTEMIC SCLEROSIS WITH ANTI CENTROMERE ANTIBODY AND SEVERE RAYNAUD'S PHENOMENON WITH DIGITAL ULCERS. (June 2019) - Isailovic, Natasa; Ceribelli, Angela; Gorlino, Carolina; Generali, Elena; Santis, Maria De; Caprioli, Marta; Guidelli, Giacomo Maria; Sarzi-Puttini, Piercarlo; Satoh, Minoru; Selmi, Carlo
Abstract : Background: Systemic Sclerosis (SSc) is characterized by the presence of serum autoantibodies (autoAbs) which may be crucial in the diagnosis, prediction of organ involvement, follow-up, and treatment choices. However, SSc sera can be negative for autoAbs identified using commercially available tests, and several new and rare autoAbs have been identified in the last decade with immunoprecipitation (IP) techniques. We recently reported a new IP pattern corresponding to anti-heterogeneous nuclar ribonucleoprotein (hnRNP) antibodies in a cohort of SSc patients. Objectives: To analyze the IP pattern of anti-hnRNP antibodies in SSc sera and determine their clinical and laboratory correlations. Methods: We investigated sera from 63 consecutive patients with SSc attending our Unit between 2014 and 2018, using protein-IP of 35 S-methionine-labeled K562 cell extract followed by SDS-PAGE and autoradiography, and IP-Western Blot for hnRNP-L and C1+C2 following established protocols. Clinical charts were used to analyze clinical and laboratory data for possible statistical correlations, performed by Prism (GraphPad Software 4.0, Fisher exact test) with statistical significance set at p values <0.05. Results: We identified a new protein-IP pattern characterized by a set of several proteins of 140/40-25kD in 8/63 (13%) SSc sera (Figure panel A). This IP pattern corresponds to the hnRNP complex which is composed of several proteins and RNAs involved in RNA processing and splicing. These proteins have molecular weights ranging between 32 and 45kD as the set of proteins we identified in our experiments. To define the 140/40-25kD pattern identified in 8 SSc cases, we performed IP-WB using two anti-hnRNP antibodies selected by the molecular weight of the target antigen. We tested anti-hnRNP C1+C2 and anti-hnRNP L monoclonal antibodies in these 8 samples after preparation by crosslinking of IgG to PAS beads and protein-IP protocol, followed by WB (Figure panel B). Results show that 5/8 SSc anti-140/40-25kD samples are positive for hnRNP L, while no reactivity was observed with hnRNP C1+C2 monoclonal antibody. We further observed that anti- hnRNP antibodies are significantly associated with serum ACApositivity (p=0.008), severe Raynaud's phenomenon with digital ulcers requiring IV prostacyclin (75%, 6/8 vs 7/54 ACA+, 13%; p=0.0006), and esophageal involvement in 4 cases. Conclusion: We identified anti-hnRNP antibodies as new target antigen of a subset of SSc patients with ACA positivity and severe peripheral vascular involvement. Additional analysis is necessary to study the several components of anti-hnRNP antibodies, and longitudinal data will provide evidence on the predictive value of this biomarker. Reference: [1] Ceribelli A, et al. J Rheumatol. 2010 Oct;37(10):2071-5 Disclosure of Interests: Natasa Isailovic: None declared, Angela Ceribelli: None declared, Carolina Gorlino: None declared, Elena Generali: None declared, Maria De Santis: None declared, Marta Caprioli: None declared, Giacomo Maria Guidelli: None declared, Piercarlo Sarzi-Puttini: None declared, Minoru Satoh: None declared, Carlo Selmi Grant/research support from: AbbVie, Janssen, MSD, Novartis, Pfizer, Consultant for: AbbVie, Alfa-Sigma, Biogen, Bristol-Myrs Squibb, Celgene, Eli-Lilly, Janssen, Merck Sharp and Dohme, Novartis, Pfizer, Roche, Sanofi-Genzyme, UCB, Speakers bureau: AbbVie, Alfa-Sigma, Biogen, Bristol-Myrs Squibb, Celgene, Eli-Lilly, Janssen, Merck Sharp and Dohme, Novartis, Pfizer, Roche, Sanofi-Genzyme, UCB